Effect of HIV infection on pre‐ and post‐liver transplant mortality in patients with organ failure. Issue 8 (8th May 2021) - Fan, X; Fang, J; Wu, X; Poulsen, K; Miyata, T; Kim, A; Yu, L; Wang, X; Zhang, X; Zhang, K; Han, Q; Liu, Z
Abstract : Objectives: Organ failure (OF), a leading cause of death in HIV‐positive individuals, is common in patients undergoing liver transplantation (LT). We examined the impact of HIV infection on pre‐ and post‐LT mortalities in cirrhotic patients stratified by the number and type of OFs. Methods: We performed a cross‐sectional study and a retrospective cohort study using the US National Inpatient Sample (NIS) and the United Network for Organ Sharing (UNOS) registry data, respectively. Patients who had not yet undergone LT from the NIS database (2010–2014) and patients undergoing LT from the UNOS database (2003–2016) were included in the study. Results: Analysis of patients (201 348) from the NIS database showed that one [adjusted odds ratio (aOR) 1.531; 95% confidence interval (CI) 1.160–2.023], two (aOR 1.624; 95% CI 1.266–2.083) or three or more OFs (aOR 1.349; 95% CI 1.165–1.562) were associated with higher pre‐LT mortality in HIV‐infected patients compared with HIV‐negative patients with the corresponding number of OFs. In patients without OF, HIV infection was not associated with increased pre‐LT mortality. UNOS data for patients undergoing LT (38 942) showed that the presence of two or more OFs was associated with increased post‐LT 1‐year mortality in HIV‐infected patients compared with non‐HIV‐infected patients with the corresponding number of OFs (aOR 2.342; 95% CI 1.576–3.480). However, in patients with no OF or only one OF, HIV infection was not associated with increased post‐LT 1‐year mortality (aOR 1.372; 95% CI 0.911–2.068). Conclusions: The results of this study emphasize the importance of preventing OF development, and justify LT for HIV‐infected patients with no or only one OF.